Pemberdayaan Masyarakat dalam Pembangunan Berkelanjutan melalui Pemanfaatan Daun Kelor (Moringa Oleifera) di Desa Kedung Sumber, Balongpanggang, Gresik - Nur Cahyadi Cahyadi; Heru Baskoro Baskoro (President University, 2020)
Community empowerment in sustainable development will not be successful without citizens’ participation, both village officials, cadres and the community itself. Community empowerment is an effort to increase the community independency, both individually and in a group. The lack of knowledge and understanding the residence of Kedung Sumber Village, Balongpanggang, Gresik regarding the use of natural resources around them, encuorages this community empowerment program. Moringa Oleifera is a local resources that could be utilized in improving the welfare of the community. This community empowerment program introduces the way how to create some products using Moringa Oleifera. Some products than can be produced are ice cream, puding, and nugget. Therefore, this program is expected to increase the community independency, both individually and in a group.